PENGARUH RASIO KEUANGAN HARGA SAHAM PERUSAHAAN SEKTOR INDUSTRI DAN SEKTOR TRANSPORTASI & LOGISTIK - Sinta Bella; Suhendro; Yuli Chomsatu Samrothun (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research aims to test and analyze the influence of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning per Share (EPS) on stock prices. The data used is secondary data originating from financial reports of companies in the industrial sector as well as the transportation and logistics sector listed on the Indonesia Stock Exchange (BEI) during the 2020 - 2023 period. The research sample was taken using a purposive sampling method, resulting in 28 companies as samples. Data analysis was carried out using multiple linear regression which was processed using SPSS version 21 software. The results showed that Return on Equity (ROE) and Earning per Share (EPS) had an influence on stock prices, while Return on Assets (ROA) and Debt to Equity Ratio (DER) has no influence on share prices. Keywords: ROA, ROE, DER, EPS, Share Price